Teacher attitudes concerning the procedures involved in teacher evaluation - Mel J. Zelenak (Educational Considerations, 1976)
Teachers who feel evaluation processes are used for instructional purposes have different attitudes about the procedure than those who feel the evaluations are used for administrative purposes.